Ethylene signaling modulates tomato pollen tube growth through modifications of cell wall remodeling and calcium gradient. (20th June 2021) - Althiab‐Almasaud, Rasha; Chen, Yi; Maza, Elie; Djari, Anis; Frasse, Pierre; Mollet, Jean‐Claude; Mazars, Christian; Jamet, Elisabeth; Chervin, Christian
SUMMARY: Ethylene modulates plant developmental processes including flower development. Previous studies have suggested ethylene participates in pollen tube (PT) elongation, and both ethylene production and perception seem critical at the time of fertilization. The full gene set regulated by ethylene during PT growth is unknown. To study this, we used various EThylene Receptor (ETR) tomato ( Solanum lycopersicum ) mutants: etr3‐ko, a loss‐of‐function (LOF) mutant; and NR ( NEVER RIPE ), a gain‐of‐function (GOF) mutant. The etr3‐ko PTs grew faster than wild‐type (WT) PTs. Oppositely, NR PT elongation was slower than in WT, and PTs displayed larger diameters. ETR mutations result in feedback control of ethylene production. Furthermore, ethylene treatment of germinating pollen grains increased PT length in etr‐ko mutants and WT, but not in NR . Treatment with the ethylene perception inhibitor 1‐methylcyclopropene decreased PT length in etr‐ko mutants and WT, but had no effect on NR . This confirmed that ethylene regulates PT growth. The comparison of PT transcriptomes in LOF and GOF mutants, etr3‐ko and NR, both harboring mutations of the ETR3 gene, revealed that ethylene perception has major impacts on cell wall‐ and calcium‐related genes as confirmed by microscopic observations showing a modified distribution of the methylesterified homogalacturonan pectic motif and of calcium load. Our results establish links between PT growth, ethylene, calcium, and cell wall metabolism, and also constitute a transcriptomic resource. Significance Statement: We deciphered the ethylene implication in tomato ( Solanum lycopersicum ) pollen tube (PT) growth. Our results (i) establish a link between cell wall remodeling and calcium and ethylene signaling, which are known to individually impact PT growth, and (ii) provide a new transcriptomic resource for this developmental stage.